DETERMINATION OF THE FROZEN STRATA THICKNESS BY RADAR SOUNDING WITH MAGNETIC FIELD PULSES - Yakupov V.S.; Yakupov M.V.; Yakupov S.V. (My University, 2003)
Degradation of frozen layers begins when average annual temperature of frozen rocks is not less than temperature of the layer thawing. Two stages of the degradation are noted. At the first stage, heating of the frozen layer occurs. At the second stage, the thawing process itself is noted. During the process, physical properties are varied. Electric conduction boundary arises. Seismic wave velocity interface is also noted. This makes it possible to apply radar method for studying the frozen layer. Mathematical model of the thawing process has been developed. Opportunity for characterizing the degradation has been shown.